Efeito do processo de recristalização na microestrutura e propriedades mecânicas da liga Ti-Nb-Sn - Andrade, Patrícia Gomes de (2017)
Currently titanium alloys metastable β type have been chosen for the biomedical applications because it has high corrosion resistance and young modulus values close to the modulus of bone. In this work we used the alloy Ti-35Nb- X Sn (0; 2,5; 5 wt%), type β-Sn, with the objective of optimizing the microstructure and mechanical properties for biomedical applications. The ingots was melted in arc furnace and subsequently homogenized at 1273K in controlled atmosphere for 12 hours in the oven and cooled, yielding a microstructure formed by the β phase. As a result, Vickers hardness testing were conducted in different regions, it was observed that the Ti-35Nb presented greater hardness value among the studied alloys, for X-ray diffraction on deformed condition all showed martensitica α” phase from the process of deformation and deformed condition 90% all samples were recrystallized.